2018
DOI: 10.30659/ekobis.19.2.171-184
|View full text |Cite
|
Sign up to set email alerts
|

Model Peningkatan Inovasi Berbasis Orientasi Pasar, Knowledge Sharing Dan Orientasi Pembelajaran Terhadap Kinerja Bisnis

Abstract: in this study is to find and analyze the influence of orientasipasar , knowledge sharingand orientation learning of the performance of business with variable innovation as variable nointervening on industrial flour tapioca in kabupaten Pati. A population that used is the owner /entrepreneurs on industrial flour tapioca in kabupaten Pati of 162 people. Based on the resultsof the spread of the questionnaire directly to owners and with using a technique the samplecollection simple random sampling, so obtained the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…In previous research conducted by Wahyono & Hutahayan (2021), showed the results that innovation was able to mediate the effect of market orientation on marketing performance. It is also supported by research conducted by Zulfa & Umam (2018) which in their study, showed similar results, where innovation was able to mediate the effect of market orientation on marketing performance.…”
Section: H5: Technology Orientation Has a Positive And Significant Ef...supporting
confidence: 69%
See 2 more Smart Citations
“…In previous research conducted by Wahyono & Hutahayan (2021), showed the results that innovation was able to mediate the effect of market orientation on marketing performance. It is also supported by research conducted by Zulfa & Umam (2018) which in their study, showed similar results, where innovation was able to mediate the effect of market orientation on marketing performance.…”
Section: H5: Technology Orientation Has a Positive And Significant Ef...supporting
confidence: 69%
“…Other research by Asashi & Sukaatmadja (2017) shows the results that market orientation has a positive and significant effect on innovation; supported by research by Zulfa & Umam (2018), which in their study, showed positive and significant results. Likewise with the technology orientation towards innovation, in the research of Widiarta et al (2020) and Chi (2021), found that technology orientation had a significant positive effect on innovation.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation